Return to play and performance after shoulder instability in National Basketball Association athletes - Lu, Y.; Okoroha, K. R.; Patel, B. H.; Nwachukwu, B. U.; Baker, J. D.; Idarraga, A. J.; Forsythe, B. (Journal of Shoulder and Elbow Surgery, 2020)
Hypothesis: We hypothesized that players in the National Basketball Association (NBA) who sustained a shoulder destabilizing injury could return to play (RTP) successfully at a high rate regardless of treatment type.